Extended Lindley Distribution with Applications - Chhetri, Sher; Mdziniso, Nonhle; Ball, Cory (Revista Colombiana de Estadística, 2022)
In this work, we propose a three-parameter generalized Lindley distribution using the cubic rank transmutation map approach by Granzotto, Louzada & Balakrishnan (2017). We derive expressions for several mathematical properties including moments and moment generating function, mean deviation, probability weighted moments, quantile function, reliability analysis, and order statistics. We conducted a simulation study to assess the performance of the maximum likelihood estimation procedure for estimating model parameters. The flexibility of the proposed model is illustrated by analyzing two real data sets.